AN EXAMINATION OF LOCALS' ATTITUDES - Gursoy, D; Chi, C.; Dyer, P. (Elsevier Ltd, 2009)
This study examines local residents' attitudes and the antecedents of those attitudes towards two different types of tourism development: mass tourism and alternative tourism. Mass tourism development is defined as attractions and facilities designed to accommodate a large number of tourists. Alternative tourism development is defined as attractions and facilities designed for ecotourism, cultural heritage tourism and outdoor recreational tourism activities. A survey was conducted on residents of Sunshine Coast, Australia. Findings show positive relationships between tourism development and perceptions of positive impacts and negative relationships between negative impacts perceptions and support for development